2015
DOI: 10.3389/fpsyg.2015.01895
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Resilience, and Burnout Subtypes in Primary Care Physicians: The Possible Mediating Role of Positive and Negative Affect

Abstract: Purpose: Primary care health professionals suffer from high levels of burnout. The aim of the present study was to evaluate the associations of mindfulness and resilience with the features of the burnout types (overload, lack of development, neglect) in primary care physicians, taking into account the potential mediating role of negative and positive affect.Methods: A cross-sectional design was used. Six hundred and twenty-two Spanish primary care physicians were recruited from an online survey. The Mindful At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 58 publications
7
81
3
1
Order By: Relevance
“…The under-challenged subtype seems to be a very affected profile that could be using cynicism as a dysfunctional coping strategy based on cognitive avoidance [39], leading to depersonalized attitudes, as it has been observed in physicians and nurses in other works [78,79]. The distance from obligations and detachment from tasks, workmates, and patients this attitude entails might reduce the adaptive ability at work, eroding possible positive affectivity derived from a job well done and from positive relationships, promoting negative affectivity, and exacerbating a lack of development, as has been previously proposed in PC physicians [80].…”
Section: The Bcsq and Other Constructsmentioning
confidence: 83%
“…The under-challenged subtype seems to be a very affected profile that could be using cynicism as a dysfunctional coping strategy based on cognitive avoidance [39], leading to depersonalized attitudes, as it has been observed in physicians and nurses in other works [78,79]. The distance from obligations and detachment from tasks, workmates, and patients this attitude entails might reduce the adaptive ability at work, eroding possible positive affectivity derived from a job well done and from positive relationships, promoting negative affectivity, and exacerbating a lack of development, as has been previously proposed in PC physicians [80].…”
Section: The Bcsq and Other Constructsmentioning
confidence: 83%
“…Results from longitudinal studies suggest that this characteristic is stable over time (Black, Sussman, Johnson, & Milam, ). Researchers have also found that mindfulness is a strong predictor of resilience among clinical and general population samples (Keye & Pidgeon, ; Montero‐Martin et al, ; Pidgeon & Keye, ). Indeed, some investigators now conceptualise mindfulness as an essential component of resilience, especially resilience against trauma (Thompson, Arnkoff, & Glass, ).…”
Section: Factors Associated With Risk For Depression Relapse or Recurmentioning
confidence: 99%
“…Previous research suggests that LKM is linked to increased mindfulness and self‐compassion (Galante, Galante, Bekkers, & Gallacher, ). In addition, mindfulness and self‐compassion scores appear to be negatively correlated to burnout (Barnard & Curry, ; Luken & Sammons, ; Montero‐Marin et al, , ). Given these findings, burnout resilience was operationalised as increased scores on mindfulness and self‐compassion outcomes.…”
Section: Present Studymentioning
confidence: 99%